Football training over 5 years is associated with preserved femoral bone mineral density in men with prostate cancer. (12th July 2018) - Uth, J.; Fristrup, B.; Haahr, R. D.; Brasso, K.; Helge, J. W.; Rørth, M.; Midtgaard, J.; Helge, E. W.; Krustrup, P.
Abstract : This study investigated the association between long‐term adherence to football training and retaining bone mineralization and physical capacity in men with prostate cancer (PCa) managed with androgen deprivation therapy (ADT). Patients completing follow‐up at 32 weeks in the FC Prostate Randomized Controlled Trial (RCT) in 2012 or 2013 were invited to 5‐year follow‐up assessments in May 2017 (n = 30). Changes in physiological outcomes over time between the football participants (FTG) and nonparticipants (CON) were examined. Twenty‐two men accepted the invitation of which 11, aged 71.3 ± 3.8 years, had continued to play self‐organized football 1.7 (SD 0.5) times per week for 4½ years (±8 months). At 5 years, right femoral neck bone mineral density (BMD) had improved significantly in the FTG compared to CON ( P = .028). No other significant between‐group differences were observed. In FTG, RHR decreased by 4.3 bpm ( P = .009) with no changes in CON. Muscle mass, knee‐extensor muscle strength, VO2 max, and postural balance decreased in both groups. In FTG, the fraction of training time with HR between 80%‐90% or >90% of HRmax was 29.9% (SD 20.6) and 22.8% (SD 28.7), respectively. Average distance covered during 3 × 20 minutes of football training was 2524 m (SD 525). Football training over a 5‐year period was associated with preserved femoral neck BMD in elderly men with PCa managed on ADT. Intensity during football training was >80% of HRmax for 51% of training time after 5 years. Body composition and physical capacity deteriorated over 5 years regardless of football participation.